Acoustic emissions associated with stress-induced twin boundary mobility in Fe7Pd3 ferromagnetic shape memory alloys. (October 2017) - Bischoff, A.J.; Mayr, S.G.
Abstract: Twin boundary mobility is an essential prerequisite for the occurrence of magnetic field induced reversible strains in the ferromagnetic shape memory alloy Fe7 Pd3 . To study the behavior of twin boundaries, an abrupt movement of these structures is locally induced by nanoindentation while concomitant acoustic emissions are detected. In martensitic Fe7 Pd3 bulk sample acoustic emissions can be correlated to pop-in events in the force-depth curves of the nanoindentation indicating twin boundary movement. In contrast, analogous experiments on freestanding Fe7 Pd3 thin films indicate an insufficient hindering of twin boundary movements within the samples so that no abrupt dislocation displacement bursts take place. Graphical Abstract: